Comparison of Plasmid Profiles and Antimicrobial Resistance Patterns of S. enteritidis Isolates in Thailand - Sumalee Boonmar; Wichai Suphasindhu; Benjamas Intarasri; Aroon Bangtrakulnonth (Agriculture and Natural Resources, 2002)
Two hundred isolates of S. enteritidis from human and chicken meat in Thailand between 1990 and 1997 were studied for antimicrobial susceptibility using disk diffusion method. The results showed that 40% of the isolates from both human and chicken meat were susceptible to all 10 antimicrobial agents, on the other hand 44-50% of the isolates from human and chicken meat were resistant to cefotaxime (CTX). Only 40% of the isolates from both susceptible group and CTX resistant group were sampled to analyse for plasmid using modified method of Kado and Liu. Most isolates contained a single 55 kilobases (kb) plasmid. Our study revealed that even the isolates from human and from chicken meat had different antimicrobial susceptibility patterns, they contained the same size of plasmid which indicated a close correlation between isolates and were derived from the same source.